Economic Crime as a Category of Criminal Research - VILKS, Andrejs; KIPANE, Aldona (Journal of Advanced Research in Law and Economics, 2019)
The relevance of the study is due to the fact that in the current period of the development of the world society, under certain conditions of criminalization, the importance of criminological inquiry is growing. In this context, the article aims to analyze the fact that, unlike other crimes, economic crimes may continue to increase in the coming years, adversely affecting economic, national and international security situations. Leading approach to the study of this problem is the descriptive method that has afforded revealing peculiarities of the criminal groups of an economic nature that accumulate large and hard-to-identify financial and material resources, and their activities are transnational in nature. The materials of the paper imply the practical significance for the university teachers of the legal specializations.